A Comprehensive Phenotypic Investigation of the “Pod-Shattering Syndrome” in Common Bean - Murgia, Maria L.; Attene, Giovanna; Rodriguez, Monica; Bitocchi, Elena; Bellucci, Elisa; Fois, Davide; Nanni, Laura; Gioia, Tania; Albani, Diego M.; Papa, Roberto; Rau, Domenico (Frontiers in Plant Science, 2017)
Seed shattering in crops is a key domestication trait due to its relevance for seed dispersal, yield and fundamental questions in evolution (e.g. convergent evolution). Here, we focused on pod shattering in common bean (Phaseolus vulgaris L.), the most important legume crop for human consuption in the world. With this main aim, we developed a methodological pipeline that comprises a thorough characterization under field conditions, including also the chemical composition and histological analysis of the pod valves. The pipeline was developed based on the assumption that the shattering trait itself can be treated in principle as a ‘syndrome’ (i.e., a set of correlated different traits) at the pod level. We characterized a population of 267 introgression lines that were developed ad hoc to study shattering in common bean. Three main objectives were sought: 1) to dissect the shattering trait into its ‘components’, of level (percentage of shattering pods per plant) and mode (percentage of pods with twisting or nontwisting valves); 2) to test whether shattering is associated to the chemical composition and/or the histological characteristics of the pod valves; and 3) to test the associations between shattering and other plant traits. We can conclude the following: very high shattering levels can be achieved in different modes; shattering resistance is mainly a qualitative trait; and high shattering levels depend on high carbon and lignin contents of the pod valves and on specific histological charaterstics of the ventral sheath and the inner fibrous layer of the pod wall. Our data also suggest that shattering comes with a ‘cost’, as it is associated with low pod size, low seed weight per pod, high pod weight, and low seed to pod-valves ratio; indeed, it can be more exaustively described as a syndrome at the pod level. Our work suggests that the valve chemical composition (i.e. carbon and lignin content) can be used for a high troughput phenotyping procedures for shattering phenotyping. Finally, we believe that the application of our pipeline will greatly facilitate comparative studies among legume crops, and gene tagging.